USE OF THE THERMOVISION TO INCREASE SAFETY IN OPERATING OF THE MECHANICAL SYSTEMS - Marin NEACSA; George ADÎR; Victor ADÎR; Ancuta ADÎR (Fiabilitate şi Durabilitate)
In this paper is presented the way we can use the thermovision in detecting of the degradationprocesses of the mobile mechanical systems. It is also presented a method for establishing of theprofitableness in using thermovision to identify priority applications of this technology